2013
DOI: 10.1542/hpeds.2012-0079
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Abstinence Syndrome Management From Prenatal Counseling to Postdischarge Follow-up Care: Results of a National Survey

Abstract: There is considerable diversity in the management of neonatal abstinence syndrome. Alternative management strategies, including prenatal counseling and home treatment programs, need to be explored to improve overall patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…2,[8][9][10][11][12][13][14] Newborns with NAS are typically cared for in NICUs, where daily cost of care is high, and many of the preceding interventions are difficult to institute. 15,16 At project outset at our hospital, there was not a coordinated, standardized system that determined when, where, and how newborns with NAS would be cared for, and expectations for family participation in care were variable. The aim of this project was to improve the care of opioid-exposed newborns by involving families, standardizing assessment and treatment, and transitioning to rooming-in for the full hospital stay.…”
Section: Methodsmentioning
confidence: 99%
“…2,[8][9][10][11][12][13][14] Newborns with NAS are typically cared for in NICUs, where daily cost of care is high, and many of the preceding interventions are difficult to institute. 15,16 At project outset at our hospital, there was not a coordinated, standardized system that determined when, where, and how newborns with NAS would be cared for, and expectations for family participation in care were variable. The aim of this project was to improve the care of opioid-exposed newborns by involving families, standardizing assessment and treatment, and transitioning to rooming-in for the full hospital stay.…”
Section: Methodsmentioning
confidence: 99%
“…At present, the modified Finnegan scores remains the most common tool that is used. 126,127 The Finnegan scoring system is used for opioid and nonopioid withdrawal assessment. 70,96 Shortened or simplified versions of these scores have met with little success.…”
Section: Managementmentioning
confidence: 99%
“…127,145 Morphine decreases the incidence of seizures, improves feeding, eliminates diarrhea, decreases agitation, and can control severe symptoms. 146 However, morphine treatment also prolongs the length of hospital stay.…”
Section: Pharmacological Carementioning
confidence: 99%
See 1 more Smart Citation
“…Although NICU settings provide the highest level acute care, they may separate the dyad which creates barriers to breastfeeding and rooming in both of which may decrease length of treatment and hospital stay for NAS (26, 27). Holmes et al demonstrated decreased hospital cost and length of stay for infants with NAS who experienced full rooming-in for observation and treatment on mother-infant pediatric units (25)**.…”
Section: Where To Treat Nasmentioning
confidence: 99%